A Novel Concept of Electron–Hole Enhancement for Superjunction Reverse-Conducting Insulated Gate Bipolar Transistor with Electron-Blocking Layer - Zhigang Wang; Chong Yang; Xiaobing Huang (Micromachines, 2023)
A novel snapback-free superjunction reverse-conducting insulated gate bipolar transistor (SJ-RC-IGBT) is proposed and verified by simulation. In the SJ-RC-IGBT, the parasitic P/N/P/N structure as thyristor or Shockley diode demonstrates large conductivity due to an overabundance of carriers for reverse conduction. By preventing electrons from leaking across the N+ region at the collector side, the extra electron-blocking (EB) layer introduced in the SJ-RC-IGBT can dramatically enhance electron–hole pairs in the N/P-pillars. Hence, the SJ-RC-IGBT demonstrates a low on-state voltage (Von). In addition, snapback-free characteristics and a large safe operating area (SOA) are also achieved in the SJ-RC-IGBT. During the turn-off process, a significant amount of electrons are extracted by parasitic MOS across the EB layer at the collector side to decrease the turn-off loss (Eoff). According to the optimized results, the SJ-RC-IGBT with EB layer obtains an ultralow Eoff of 3.9 mJ/cm2 at Von = 1.38 V with 88% and 81% decreases, respectively, compared with the conventional reverse-conducting IGBT (CRC-IGBT) and superjunction IGBT (SJ-IGBT).